2011
DOI: 10.1002/ieam.261
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risks to ground-feeding songbirds from lead in the Coeur d'Alene Basin, Idaho, USA

Abstract: Previous assessment of ecological risks within the Coeur d'Alene River Basin identified Pb as a key risk driver for ground-feeding songbirds. Because this conclusion was based almost exclusively on literature data, its strength was determined to range from low to moderate. With the support of the US Environmental Protection Agency (USEPA), the US Fish and Wildlife Service collected site-specific data to address the uncertainty associated with Pb risks to songbirds. These data, plus those from the previous Coeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…These dose–response assessments were typically applied in the detailed or baseline risk analyses to further refine ecological risks. For example, a dose–response analysis of dietary Pb in 3 ground‐feeding songbird species recently was used to aid in the determination of preliminary remediation goals for the Coeur d'Alene River basin in Idaho and Washington (Sample et al 2011). Although the calculated ED20 (9.9 mg × kg −1 × d −1 ) based on a multiparameter logistic model using data from a chicken reproduction study was higher than the reported LOAEL (3.52 mg × kg −1 × d −1 ) or NOAEL (0.35 mg × kg −1 × d −1 ), the resulting calculated soil preliminary remediation goal was comparable to clean up values previously derived for waterfowl and humans, and therefore considered appropriately protective of ground‐feeding songbirds.…”
Section: Trv Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These dose–response assessments were typically applied in the detailed or baseline risk analyses to further refine ecological risks. For example, a dose–response analysis of dietary Pb in 3 ground‐feeding songbird species recently was used to aid in the determination of preliminary remediation goals for the Coeur d'Alene River basin in Idaho and Washington (Sample et al 2011). Although the calculated ED20 (9.9 mg × kg −1 × d −1 ) based on a multiparameter logistic model using data from a chicken reproduction study was higher than the reported LOAEL (3.52 mg × kg −1 × d −1 ) or NOAEL (0.35 mg × kg −1 × d −1 ), the resulting calculated soil preliminary remediation goal was comparable to clean up values previously derived for waterfowl and humans, and therefore considered appropriately protective of ground‐feeding songbirds.…”
Section: Trv Analysismentioning
confidence: 99%
“…For example, the USEPA Eco‐SSL TRV derivation procedure uses an inferential statistical method (NOAELs and LOAELs), which historically has been standard practice in regulatory ecological risk assessment. However, alternative TRV derivation procedures (i.e., the use of a species sensitivity distribution based on a population level effect concentration, ED x or benchmark dose) have been proposed (USACHPPM 2000; Allard et al 2010) and are now being implemented at a limited number of Superfund sites (Sample et al 2011). In addition, ERAs frequently are unclear (or unstated) about the uncertainty factors used to derive the TRV values (extrapolation from subchronic to chronic exposure duration), and may use different assumed food ingestion rates, body weights, and interspecies scaling factors (Duke and Taggart 2000; McDonald and Wilcockson 2003; DeMott et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some elements, such as Cd, Zn and Se, have been shown to bioaccumulate to high concentrations in earthworm tissue (Helmke et al 1979). Robins may also be at risk of poisoning by elements such as Pb (Bennett et al 2007, Sample et al 2011), which tend not to bioaccumulate in earthworm tissue but are present in the soil within an earthworm's gut. Hazards from soil ingestion and bioaccumulation are applicable to other avian species that…”
Section: Robins As Wildlife Receptors In Ecological Risk Assessmentmentioning
confidence: 99%
“…Some elements, such as Cd, Zn, and Se, have been shown to bioaccumulate to high concentrations in earthworm tissue (Helmke et al 1979). Robins may also be at risk for poisoning by elements such as Pb (Bennett et al 2007;Sample et al 2011), which tend not to bioaccumulate in earthworm tissue but are present in the soil within an earthworm's gut. Hazards from soil ingestion and bioaccumulation are applicable to other avian species that prey on earthworms, such as American woodcock, plovers, owls, kestrels, rooks, thrushes, starlings, and gulls, and to other vertebrates, such as reptiles (snakes), amphibians (toads, frogs, and newts), and mammals (shrews, moles, red foxes, and badgers) (Macdonald 1983).…”
Section: Robins As Wildlife Receptors In Ecological Risk Assessmentmentioning
confidence: 99%
“…Further, site-specific risk-based remedial goals for Pb (based on field-collected avian exposure data) that are many times the avian Eco-SSL of Pb have been identified. For example, the lowest preliminary remedial goal identified by Sample et al (2011) for songbirds exposed to Pb in soil in the Coeur d'Alene, Idaho, USA floodplain was 490 mg/kg. This value was comparable to that identified for sedimentexposed waterfowl in the Coeur d'Alene basin (530 mg/kg; USEPA 2002).…”
Section: Introductionmentioning
confidence: 99%